Two fungi associated with necrotic leaflets of areca palms (Areca catechu) - Chaiwat To-Anun (2018)
Information on fungi associated with necrotic leaflets of exotic palms in Thailand is scanty, as previous studies were mainly focused on decaying fronds. This study provides some information regarding fungi associated with necrotic leaflets of exotic palms in Thailand. Specimens in this work were collected from several locations in Chiang Mai province, including natural and planted areas. One new species, Cercospora arecacearum on areca palm (Areca catechu), is described and illustrated. An ITS sequence data analysis confirms the separation of the new Cercospora species from related taxa. Another species, Neorehmia arecae, hitherto only known from areca palm, is newly recorded for Thailand. Furthermore, Wallichia siamensis is a new host for this species. © 2009 German Mycological Society and Springer.